Contextualizing Wetlands Within a River Network to Assess Nitrate Removal and Inform Watershed Management. Issue 2 (27th February 2018) - Czuba, Jonathan A.; Hansen, Amy T.; Foufoula‐Georgiou, Efi; Finlay, Jacques C.
Abstract: Aquatic nitrate removal depends on interactions throughout an interconnected network of lakes, wetlands, and river channels. Herein, we present a network‐based model that quantifies nitrate‐nitrogen and organic carbon concentrations through a wetland‐river network and estimates nitrate export from the watershed. This model dynamically accounts for multiple competing limitations on nitrate removal, explicitly incorporates wetlands in the network, and captures hierarchical network effects and spatial interactions. We apply the model to the Le Sueur Basin, a data‐rich 2, 880 km 2 agricultural landscape in southern Minnesota and validate the model using synoptic field measurements during June for years 2013–2015. Using the model, we show that the overall limits to nitrate removal rate via denitrification shift between nitrate concentration, organic carbon availability, and residence time depending on discharge, characteristics of the waterbody, and location in the network. Our model results show that the spatial context of wetland restorations is an important but often overlooked factor because nonlinearities in the system, e.g., deriving from switching of resource limitation on denitrification rate, can lead to unexpected changes in downstream biogeochemistry. Our results demonstrate that reduction of watershed‐scale nitrate concentrations and downstream loads in the Le Sueur Basin can be most effectively achieved by increasing water residence time (by slowing the flow) rather than by increasing organic carbon concentrations (which may limit denitrification). This framework can be used toward assessing where and how to restore wetlands for reducing nitrate concentrations and loads from agricultural watersheds. Key Points: We present a framework for quantifying dynamic and spatially explicit nitrate removal and limiting factors in a wetland‐river network Nitrate removal via denitrification can be limited by either nitrate, organic carbon, or residence time depending on flow conditions Spatial context of wetlands matters as nonlinearities from resource limitations lead to unexpected changes in downstream biogeochemistry